Zeolite-based photocatalytic material with cadmium sulfide nanoflowers and nanoparticles coexisting on surface as well as preparation method and application of zeolite-based photocatalytic material

By growing cubic and hexagonal phase cadmium sulfide nanoflowers and nanoparticles coexisting on the hydrogen-type mordenite, the problems of photocorrosion and carrier recombination of traditional cadmium sulfide photocatalysts are solved, and efficient photocatalytic degradation is achieved.

CN119524912APending Publication Date: 2025-02-28XIJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411621846.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional unmodified cadmium sulfide photocatalysts have problems of photocorrosion and easy recombination of photogenerated carriers, resulting in low quantum efficiency.

Method used

Using zeolite-based photocatalytic materials that coexist cadmium sulfide nanoflowers and nanoparticles on the surface, the growth and distribution of CdS nanoparticles in two phase structures is achieved by growing CdS nanoparticles on the hydrogen mordenite by using the electric field of the zeolite.

Benefits of technology

The photocatalytic degradation efficiency is improved, the carrier recombination is reduced, the photoelectron transfer efficiency is accelerated, and the stability of photocatalytic materials is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524912A_ABST
    Figure CN119524912A_ABST
Patent Text Reader

Abstract

The invention discloses a zeolite-based photocatalytic material with cadmium sulfide nanoflowers and nanoparticles coexisting on the surface and a preparation method and application thereof.The preparation method includes the steps that HMOR serves as a carrier, CdS nanoparticles grow on HMOR zeolite, growth and distribution of the CdS nanoparticles of two phase structures on the surfaces of the HMOR zeolite are achieved under the action of an HMOR electric field, the content of ammonia water in a system is controlled, and the photocatalytic material is prepared. Cadmium ions and a sulfur source react on the surface of HMOR, the zeolite-based photocatalytic material with cadmium sulfide nanoflowers and nanoparticles coexisting on the surface is prepared, phase heterojunctions between cubic-phase CdS and hexagonal-phase CdS can effectively promote separation of photo-induced electron-hole pairs, the CdS nanoparticles and HMOR can generate a synergistic effect, methylene blue is subjected to photocatalytic degradation, and the photocatalytic effect is good. The removal efficiency of methylene blue is improved. HMOR is used as an electron acceptor, can accelerate the transfer efficiency of photoelectrons, inhibit the recombination of charges and improve the photocatalytic efficiency, and has good environmental protection benefits and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to photocatalytic materials, and specifically relates to a zeolite-based photocatalytic material with cadmium sulfide nanoflowers and nanoparticles coexisting on the surface, and a preparation method and application thereof. Background Art

[0002] As the energy crisis becomes increasingly severe, sunlight as a renewable clean energy has received widespread attention from the international community. Using solar energy to activate photocatalysts at room temperature and drive redox reactions can achieve complete decomposition of pollutants without secondary pollution. Narrow-bandgap cadmium sulfide photocatalysts have excellent visible light response capabilities and are an important photocatalytic material with the greatest potential for environmental purification and solar energy conversion. They are the current research frontier and hotspot in the fields of international environment and energy.

[0003] However, traditional unmodified CdS photocatalysts suffer from severe photocorrosion and easy recombination of photogenerated carriers, resulting in low CdS photocatalytic quantum efficiency. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a zeolite-based photocatalytic material with coexisting cadmium sulfide nanoflowers and nanoparticles on the surface, and a preparation method and application thereof, which has good electron transport performance and photocatalytic stability, high photocatalytic degradation efficiency and short response time.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a zeolite-based photocatalytic material with cadmium sulfide nanoflowers and nanoparticles coexisting on the surface comprises the following steps:

[0007] Step 1, adding hydrogen-type mordenite into a round-bottom flask, adding deionized water for ultrasonic dispersion to make it evenly mixed, to obtain a dispersion;

[0008] Step 2: Sodium citrate is taken and completely dissolved in deionized water, and then cadmium chloride is added and stirred until fully dissolved to obtain a mixed solution, the mixed solution is added to the dispersion prepared in step 1, ammonia water is added so that the mass fraction of ammonia in the entire reaction system is 0.67wt% to 3.35wt%, thiourea is added, the bottle stopper is tightly closed, and the oil bath is heated at a temperature of 60 to 100° C. for 150 to 180 minutes until the color of the mixed solution changes from colorless to orange-yellow, and then the solid is collected by centrifugation, and after washing and drying, the CdS@HMOR composite photocatalytic material is obtained;

[0009] The mass ratio of hydrogen-type mordenite, sodium citrate, cadmium chloride and thiourea is 249.5-250.7: 89.7-91.2: 49.2-50.3: 20.4-21.5.

[0010] The present invention also has the following technical features:

[0011] Preferably, the ultrasonic frequency in step 1 is 55 kHz and the time is 20 to 30 minutes.

[0012] Preferably, the rotation speed of the centrifuge during the centrifugation process in step 2 is 10000 rpm to 12000 rpm.

[0013] Preferably, the washing in step 2 is performed by washing with deionized water for 3 to 5 times.

[0014] Preferably, the drying in step 2 is performed in a drying oven at 60-80° C. for 8-12 hours.

[0015] The present invention also protects a zeolite-based photocatalytic material prepared by the method as described above, with cadmium sulfide nanoflowers and nanoparticles coexisting on the surface, and its application in visible light catalytic degradation of organic matter or medium light catalytic decomposition of water to produce hydrogen.

[0016] Compared with the prior art, the present invention has the following technical effects:

[0017] The invention prepares a zeolite-based photocatalytic material with coexisting cadmium sulfide nanoflowers and nanoparticles on the surface by adjusting appropriate temperature and ammonia concentration. HMOR is used as a carrier, CdS nanoparticles are grown on the HMOR zeolite, and the growth and distribution of CdS nanoparticles with two phase structures on the surface are achieved by using the HMOR electric field. The cadmium sulfide on the surface of the hydrogen-type mordenite has nano-sheet and nano-granular morphologies, which correspond to two cadmium sulfide crystal phases and are in close contact with each other. The phase heterojunction between the cubic phase CdS and the hexagonal phase CdS can effectively promote the separation of photogenerated electron-hole pairs, and the CdS nanoparticles and HMOR can produce a synergistic effect. The hydrogen-type mordenite can stabilize the cadmium sulfide structure on its surface as a support with a large specific surface area, and can also be used as an electron acceptor to form effective electron transmission between cadmium sulfides of different phases on the surface, thereby reducing the recombination between carriers, accelerating the transfer efficiency of photoelectrons, inhibiting the recombination of charges, and improving the photocatalytic efficiency.

[0018] In the preparation process of the present invention, by controlling the mass ratio of ammonia water to hydrogen-type mordenite, not only can the reaction of cadmium ions and sulfur sources on the surface of HMOR be achieved, but also the waste of raw materials and the load of subsequent washing and impurity removal processes caused by excessive addition can be avoided; and low-cost HMOR and CdS nanoparticles are combined to prepare high-performance CdS@HMOR composite photocatalytic materials, which reduces the amount of cadmium sulfide used alone as a photocatalyst in the prior art, not only improves the catalytic degradation rate of methylene blue, but also saves costs, and has good environmental and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the synthesis of CdS@MOR composite photocatalytic materials in Examples 1 to 5;

[0020] Figure 2 X-ray diffraction spectra of the products prepared in Examples 1 to 7;

[0021] Figure 3 is the Raman spectrum of the product prepared in Example 4;

[0022] Figure 4 The XPS spectra of the products prepared in Example 4 and Comparative Example 1 are shown in FIG.

[0023] Figure 5 is a scanning electron microscope image of the products prepared in Examples 1 to 7;

[0024] Figure 6 The scanning electron microscope image and elemental mapping image of the product prepared in Example 4;

[0025] Figure 7 The photocatalytic activity, kinetic constants and degradation efficiency diagrams of the products prepared in Examples 1 to 7;

[0026] Figure 8 This is a diagram showing the growth mechanism of cadmium sulfide on the surface of hydrogen-type mordenite prepared in Examples 1 to 7. DETAILED DESCRIPTION

[0027] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0028] The ammonia water used in the following examples is ammonia water with a mass fraction of 25%.

[0029] Example 1

[0030] This example provides a method for preparing a CdS@HMOR composite photocatalytic material. The preparation process is as follows: Figure 1 As shown, the specific steps are as follows:

[0031] Take 0.5g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 20min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.18g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.1g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 0.67wt%, then add 2.8mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 80℃ for 180min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 10000rpm, wash it with deionized water 3 times, collect the powder and dry it in a drying oven at 60℃ for 8 hours to obtain CdS@HMOR composite photocatalytic material.

[0032] Example 2

[0033] This example provides a method for preparing a CdS@HMOR composite photocatalytic material, and the preparation process is as follows:

[0034] Take 0.499g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 25min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.179g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.098g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 1.34wt%, then add 2.72mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 80℃ for 150min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 11000rpm, wash it with deionized water 4 times, collect the powder and dry it in a drying oven at 70℃ for 10 hours to obtain CdS@HMOR composite photocatalytic material.

[0035] Example 3

[0036] This example provides a method for preparing a CdS@HMOR composite photocatalytic material, and the preparation process is as follows:

[0037] Take 0.5014g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 30min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.1824g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.1006g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 2.01wt%, then add 2.86mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 80℃ for 160min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 12000rpm, wash it with deionized water 5 times, collect the powder and dry it in a drying oven at 80℃ for 8 hours to obtain CdS@HMOR composite photocatalytic material.

[0038] Example 4

[0039] This example provides a method for preparing a CdS@HMOR composite photocatalytic material, and the preparation process is as follows:

[0040] Take 0.5g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 20min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.18g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.1g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 2.68wt%, then add 2.8mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 80℃ for 180min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 10000rpmrpm, wash it with deionized water 5 times, collect the powder and dry it in a drying oven at 60℃ for 12 hours to obtain CdS@HMOR composite photocatalytic material.

[0041] Example 5

[0042] This example provides a method for preparing a CdS@HMOR composite photocatalytic material, and the preparation process is as follows:

[0043] Take 0.5g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 20min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.18g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.1g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 3.35wt%, then add 2.8mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 80℃ for 180min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 10000rpmrpm, wash it with deionized water 5 times, collect the powder and dry it in a drying oven at 60℃ for 12 hours to obtain CdS@HMOR composite photocatalytic material.

[0044] Example 6

[0045] This example provides a method for preparing a CdS@HMOR composite photocatalytic material, and the preparation process is as follows:

[0046] Take 0.5g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 20min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.18g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.1g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 2.68wt%, then add 2.8mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 60℃ for 180min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 12000rpm, wash it with deionized water 5 times, collect the powder and dry it in a drying oven at 60℃ for 12 hours to obtain CdS@HMOR composite photocatalytic material.

[0047] Example 7

[0048] This example provides a method for preparing a CdS@HMOR composite photocatalytic material, and the preparation process is as follows:

[0049] Take 0.5g hydrogen-type mordenite and add it to a 100mL flask, add 80mL deionized water and ultrasonically disperse it for 20min to mix it evenly, the ultrasonic frequency is 55kHz, take 0.18g sodium citrate and dissolve it completely in 6mL deionized water, stir for 5min, and at the same time, dissolve 0.1g cadmium chloride completely in 10mL deionized water, stir for 5min, and move the above solution mixture into the round-bottom flask containing the above hydrogen-type mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 2.68wt%, then add 2.8mL thiourea (0.015g / mL) to the mixed solution, cover the bottle cap and heat it in an oil bath at 100℃ for 180min, the color of the mixed solution changes from colorless to orange-yellow, and then collect the powder by centrifugation, the speed of the centrifuge is 12000rpm, wash it with deionized water 5 times, collect the powder and dry it in a drying oven at 60℃ for 12 hours to obtain CdS@HMOR composite photocatalytic material.

[0050] Comparative Example 1

[0051] The preparation of HMOR-free CdS as a photocatalytic material includes the following specific synthesis steps:

[0052] Take 0.18g of sodium citrate and dissolve it completely in 6mL of deionized water, stir for 5min, and at the same time, dissolve 0.1g of cadmium chloride completely in 10mL of deionized water, stir for 5min, mix the above solutions and move them into the round-bottom flask of the above hydrogen-containing mordenite mixed solution, add ammonia water so that the mass fraction of ammonia in the whole reaction system is 2.68wt%, then add 2.8mL of thiourea (0.015g / mL) to the mixed solution, cover the bottle stopper and heat it in an 80℃ oil bath for 180min, the color of the mixed solution changes from colorless to orange-yellow, then centrifuge to collect the powder, the speed of the centrifuge is 12000rpm, wash with deionized water 5 times, collect the powder and dry it in a drying oven at 60℃ for 12 hours to obtain a CdS composite photocatalytic material without HMOR.

[0053] Experimental Example 1

[0054] X-ray diffraction spectrum (XRD):

[0055] The structures of the different CdS@HMOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 7 were characterized and compared with CdS and HMOR. The obtained XRD patterns are shown in Figure 2 shown.

[0056] from Figure 2In a, it can be seen that in addition to the characteristic peaks of hydrogen-type mordenite itself, the cadmium sulfide crystal phase in the CdS@HMOR synthesized at 60°C tends to be more cubic, and its corresponding (111)(200) crystal planes are more prominent; compared with the sample synthesized at 60°C, the cadmium sulfide hexagonal phase of the composite material we prepared at 80°C corresponds to the (002), (101) planes have higher crystallinity, and the characteristic peaks corresponding to the cubic system can still be observed; but when the temperature is 100°C, the (200) crystal plane corresponding to the cubic phase of cadmium sulfide gradually decreases, proving that as the temperature increases, it is not conducive to the formation of the cubic phase, and the growth of cadmium sulfide crystals on the surface of hydrogen-type mordenite tends to be more hexagonal. From Figure 2 b It can be seen that by adjusting the ammonia content in the system to 0.67wt%~3.35wt%, different prepared photocatalytic composite materials of cadmium sulfide with different crystal phases based on hydrogen-type mordenite are obtained. From the illustrations in the figure, it can be seen that the (200) crystal plane representing the cubic crystal system and the (100) crystal plane representing the hexagonal crystal system change with the increase of ammonia concentration. When the ammonia content is 1.34wt% and below, the cadmium sulfide on the surface of hydrogen-type mordenite is a pure cubic phase. At 2.01wt%, part of the cubic phase of cadmium sulfide begins to transform into a hexagonal phase; with the increase of ammonia content, the cubic phase and the hexagonal phase form a coexistence state on the surface of hydrogen-type mordenite; when the ammonia content is 3.35wt%, the cubic phase of cadmium sulfide on the surface of hydrogen-type mordenite is completely transformed into a hexagonal phase.

[0057] Experimental Example 2

[0058] Raman spectroscopy:

[0059] The structure of the CdS@HMOR composite photocatalytic material obtained by the technical solution of Example 4 was characterized, and the Raman image obtained was as follows: Figure 3 As shown; the ammonia content is 2.68wt% CdS@HMOR at ~295cm -1 and ~596cm -1 The Raman scattering at 482cm corresponds to the cubic LO phonon and the hexagonal Al(LO)+E1(LO) phonon, respectively. It is proved that the CdS grown on the HMOR surface belongs to the coexistence of hexagonal and cubic phases. It is proved that the cadmium sulfide grown on the surface of hydrogen-type mordenite belongs to the coexistence of hexagonal and cubic phases. In the Raman spectrum of CdS@HMOR with an ammonia content of 2.68wt%, in addition to the characteristic peaks of CdS cubic and hexagonal phases, 482cm -1 The corresponding peak is the characteristic peak of the HMOR four-membered ring.

[0060] Experimental Example 3

[0061] XPS spectrum (XPS):

[0062] The structures of different CdS@HMOR composite photocatalytic materials obtained by the technical solutions of Example 4 and Comparative Example 1 were characterized and compared with CdS and HMOR. The XPS spectra obtained are shown in FIG. Figure 4 shown.

[0063] Figure 4 The XPS spectra of CdS@HMOR and CdS with high resolution Cd3d (a, b) and S2p (c, d) at 2.68 wt% ammonia concentration are shown in Figure 2. Peaks at 404.9 eV and 411.7 eV can be observed in CdS, corresponding to Cd3d 5 / 2 and Cd3d 3 / 2 In addition, the peaks at 161.2 eV and 162.3 eV correspond to S2p 3 / 2 and S2p 1 / 2 . After comparison, it was found that the Cd3d and S2p electron binding energies of CdS@HMOR changed compared to CdS. The change in binding energy is related to the change in electron density on the catalyst surface, indicating that there is electron transfer in the CdS@HMOR composite material, proving that there is a close interaction between HMOR and CdS. The XPS results show that the CdS@HMOR composite material was successfully synthesized, and there is a close interaction between CdS and HMOR with a heterojunction.

[0064] Experimental Example 4

[0065] Scanning electron microscope (SEM):

[0066] The morphology of different CdS@HMOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 7 was characterized and compared with CdS and HMOR. The SEM images obtained are as follows: Figure 5 , as shown in 6.

[0067] Figure 5 (aj) is the scanning electron microscope image of CdS@HMOR composites prepared under different ammonia concentrations. When the ammonia content is less than 1.34wt%, the cadmium sulfide grown on the surface of hydrogen-type mordenite is dispersed in nanoparticles and forms a close contact with the hydrogen-type mordenite. This granular cadmium sulfide belongs to the cubic phase structure; with the increase of ammonia content, plate-like hexagonal cadmium sulfide gradually forms on the surface of hydrogen-type mordenite, and granular cubic cadmium sulfide can also be seen coexisting with it. They cover the surface of hydrogen-type mordenite and contact each other. This contact is conducive to the charge transfer between them and to improve the efficiency of the catalytic reaction; when the ammonia content is 3.35wt%, the surface of hydrogen-type mordenite is basically covered by plate-like hexagonal cadmium sulfide, and no granular morphology of cubic cadmium sulfide is seen. The results show that with the increase of ammonia content, CdS on the HMOR surface will change from tending to grow in the cubic phase to tending to grow in the hexagonal phase.

[0068] Figure 6 (ad) shows the scanning electron microscope image of the CdS@HMOR composite material with an ammonia concentration of 2.68wt%. It can be seen from the figure that hexagonal cadmium sulfide with a lamellar morphology and cubic cadmium sulfide with a granular morphology are grown on the surface of hydrogen-type mordenite. Compared with the granular cubic cadmium sulfide on the surface of the CdS@HMOR composite material with an ammonia concentration of 1.34wt%, there are more cubic cadmium sulfide particles in the composite material where the two phases coexist. This is because the increase in ammonia content is conducive to the hydrolysis of thiourea, providing a good growth environment for the growth of cadmium sulfide crystals. Moreover, with the increase in ammonia content, cadmium sulfide begins to tend to grow in the hexagonal phase and exists in the form of nanosheets on the surface of HMOR. At the same time, the element mapping diagram of the composite material is shown in Figure 2. Figure 6 As shown in (e), it can be seen that the CdS@HMOR composite material with an ammonia concentration of 2.68wt% is composed of elements such as Si, Al, O, Cd and S. The elements in the cadmium sulfide on the surface of hydrogen-type mordenite are evenly distributed on the surface, and no other impurity elements can be seen in EDS (6f). It proves that the CdS@HMOR photocatalytic material with an ammonia concentration of 2.68wt% has been successfully synthesized.

[0069] Experimental Example 5

[0070] Photocatalytic degradation of MB test:

[0071] The different CdS@HMOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 7 were tested for photocatalytic degradation of MB. Before the photocatalytic reaction, all samples were placed in a dark environment to allow them to reach adsorption and desorption equilibrium for MB. After the dark reaction for 1 hour, the synthesized samples were tested for photocatalytic degradation of MB. The results are as follows Figure 7 shown.

[0072] Figure 7 Visible light-driven photocatalytic activity (ac) of CdS@HMOR towards MB at different temperatures and different ammonia contents, their kinetic constants (df) and the degradation efficiency (gl) of the composite material.

[0073] The photocatalytic activity of the synthesized various CdS@HMOR composite materials was reflected by the degradation of methylene blue under visible light. The results are shown in Figure 7. In order to explore the photocatalytic performance of different cadmium sulfide crystal phases grown on the surface of hydrogen-type mordenite, CdS@HMOR photocatalytic materials with different ammonia concentrations and different temperatures were synthesized. Figure 7(ac) It can be seen that the degradation rate of methylene blue by photocatalytic degradation of cadmium sulfide (without HMOR) in the system without hydrogen peroxide is 40.34%. When combined with hydrogen-type mordenite, the efficiency of photocatalytic degradation of methylene blue can be effectively improved. This proves that there is a synergistic effect between HMOR and CdS, which can effectively improve the photocatalytic efficiency.

[0074] like Figure 7 As shown in (gh), the CdS@HMOR composite material synthesized at 80℃ has a faster degradation rate and a higher degradation rate. This is because the porous structural properties of HMOR are conducive to the enrichment of pollutants and increase the contact probability between pollutants and CdS on the HMOR surface. Moreover, HMOR, as an electron acceptor, is conducive to the separation of CdS charges. When the concentration of ammonia water used to synthesize the CdS@HMOR composite material is 1.34wt%, that is, when the CdS@HMOR composite material is in a cubic phase, the degradation rate of methylene blue is 73.81%; when the concentration of ammonia water used to synthesize the CdS@HMOR composite material is 3.35wt%, that is, when the CdS@HMOR composite material is in a hexagonal phase, the degradation rate of methylene blue is 79.52%; when the concentration of ammonia water used to synthesize the CdS@HMOR composite material is 2.01~2.68wt%, that is, when cubic and hexagonal cadmium sulfide coexist on the surface of hydrogen-type mordenite, the degradation rate of methylene blue is the highest. This indicates that the two-phase coexistence of cadmium sulfide on the surface of hydrogen-type mordenite has higher photocatalytic activity than that of single-phase cadmium sulfide.

[0075] like Figure 7 As shown in (g), when the ammonia content in the prepared material was 2.68wt% at 80°C, the degradation rate was 84.15%. In addition to the synergistic effect between hydrogen-type mordenite and cadmium sulfide, another reason for the improvement of the degradation performance of the composite photocatalytic material for methylene blue is the close contact between cadmium sulfide in different phases (cubic phase and hexagonal phase) on the surface of hydrogen-type mordenite. This contact is conducive to the transfer of charges and the generation of active species, thereby enhancing the photocatalytic degradation efficiency. At the same time, Figure 7 As shown in (i), when 1.5 mL of hydrogen peroxide (H2O2) was added into the system, the degradation rate of 2 wt% CdS@HMOR increased from 84.15% to 98.98%; Figure 7 As shown in (j, l), the rate constant k of 2.68wt%CdS@HMOR increased from 0.8884h -1 Enhanced to 1.9976h -1 This is because the addition of H2O2 increases the amount of ·OH generated, thereby enhancing the oxidizing property and facilitating the occurrence of photocatalytic reactions.

[0076] Experimental Example 6

[0077] The growth mechanism of different CdS@HMOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 7 was analyzed to obtain the growth mechanism of cadmium sulfide on the surface of hydrogen-type mordenite, such as Figure 8 shown.

[0078] from Figure 8 It can be seen that in the solution with thiourea and cadmium chloride as precursors, the surface electric field of hydrogen-type mordenite in the system has an influence on the surface electric field of Cd 2+ The invention has a certain attraction effect. With the addition of ammonia water of different contents, thiourea begins to hydrolyze. When the ammonia water content is low (less than 1.34wt%), the sulfur source content of thiourea hydrolyzed is very low, and cubic cadmium sulfide is more inclined to be formed on the surface of hydrogen-type mordenite. When the sulfur source content increases, hexagonal cadmium sulfide occupies a dominant position. By controlling the reaction temperature and the ammonia water content in the system (2.01-2.68wt%), cadmium sulfide with different crystal phases coexisting can be synthesized on the surface of hydrogen-type mordenite. When the ammonia water content is large (greater than 2.68wt%), a high content of sulfur is hydrolyzed. At this time, cadmium sulfide is produced through a kinetic-dominated process to generate hexagonal cadmium sulfide. As the sulfur content decreases during the reaction, the nucleation rate gradually decreases, and the process of generating cadmium sulfide is transformed from a kinetic process to a thermodynamic process, forming a state in which cubic and hexagonal cadmium sulfide coexist. In addition, it can be seen in the synthesized cadmium sulfide material that when two phases coexist, cadmium sulfide grows on the surface of hydrogen-type mordenite, it has higher photocatalytic activity. The composite of cadmium sulfide and hydrogen-type mordenite is beneficial to improving the separation rate of photogenerated carriers.

[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a zeolite-based photocatalytic material with cadmium sulfide nanoflowers and nanoparticles coexisting on the surface, characterized in that: The following steps are involved: Step 1, adding hydrogen-type mordenite into a round-bottom flask, adding deionized water for ultrasonic dispersion to make it evenly mixed, to obtain a dispersion; Step 2: Sodium citrate is taken and completely dissolved in deionized water, and then cadmium chloride is added and stirred until fully dissolved to obtain a mixed solution, the mixed solution is added to the dispersion prepared in step 1, ammonia water is added so that the mass fraction of ammonia in the entire reaction system is 0.67wt% to 3.35wt%, thiourea is added, the bottle stopper is tightly closed, and the oil bath is heated at a temperature of 60 to 100° C. for 150 to 180 minutes until the color of the mixed solution changes from colorless to orange-yellow, and then the solid is collected by centrifugation, and after washing and drying, the CdS@HMOR composite photocatalytic material is obtained; The mass ratio of hydrogen-type mordenite, sodium citrate, cadmium chloride and thiourea is 249.5-250.7: 89.7-91.2: 49.2-50.3: 20.4-21.

5.

2. The method for preparing a zeolite-based photocatalytic material with coexistence of cadmium sulfide nanoflowers and nanoparticles on the surface as claimed in claim 1, characterized in that: The ultrasonic frequency described in step 1 is 55kHz and the time is 20 to 30 minutes.

3. The method for preparing a zeolite-based photocatalytic material with coexistence of cadmium sulfide nanoflowers and nanoparticles on the surface as claimed in claim 1, characterized in that: The rotation speed of the centrifuge during the centrifugation process described in step 2 is 10000 rpm to 12000 rpm.

4. The method for preparing a zeolite-based photocatalytic material with coexistence of cadmium sulfide nanoflowers and nanoparticles on the surface as claimed in claim 1, characterized in that: The washing in step 2 is performed by washing with deionized water for 3 to 5 times.

5. The method for preparing a zeolite-based photocatalytic material with coexistence of cadmium sulfide nanoflowers and nanoparticles on the surface as claimed in claim 1, characterized in that: The drying in step 2 is carried out in a drying oven at 60 to 80° C. for 8 to 12 hours.

6. A zeolite-based photocatalytic material having cadmium sulfide nanoflowers and nanoparticles coexisting on the surface, prepared by the method according to any one of claims 1 to 5.

7. An application of the zeolite-based photocatalytic material with coexistence of cadmium sulfide nanoflowers and nanoparticles on the surface as claimed in claim 6 in the process of visible light catalytic degradation of organic matter or medium light catalytic decomposition of water to produce hydrogen.